3D simulation of AC loss in a twisted multi-filamentary superconducting wire. (June 2017) - Zhao, Junjie; Li, Yingxu; Gao, Yuanwen
Highlights: We develop a 3D model to simulate the AC loss of the twisted multi-filamentary superconducting wire. The simulation considers twisted structure of the filament. The twist pitch and magnetic field direction effects on the AC loss are investigated. The effect the non-uniform current distribution subject to the strand bending on the AC loss is discussed. Abstract: In the AC loss simulation, it is a huge challenge to model the twisted wire at the filament level, due to the complex structure as well as long-time computation consumption. In this paper, we use 3D finite-element method based on H-formulation to study the AC loss in a twisted superconducting wire. The wire is treated as a homogenous material with the anisotropic conductivity in the filament region. We quantitatively simulate the AC loss induced by the AC transport current and magnetic field profile, and the effect of the twist pitch on the AC loss. In the case of AC transport current, larger pitch length leads to higher loss, and the pitch length effect is contrary to the case of applied magnetic field. The influences of the magnetic field direction and non-uniform current distribution subjected to the strand bending are also investigated. It is observed that, the transverse magnetic field has a more significant influence on the AC loss than the longitudinal magnetic field. The non-uniform current distribution can result in a higher AC loss, compared to a corresponding uniform current distribution.